Muslim Identity Formation Within Secular Education: The Case Of Western Society: - Azmi, Diinu Tsabitul; Khoeri, Nabil Irtifa Afrizal (el-Tarbawi, 2025)
The phenomenon of secularism has created an educational space that is often detached from spiritual and religious values. For Muslim communities, particularly the younger generation growing up in Western educational systems, this has given rise to a complex identity crisis. This article aims to examine the influence of secularism on the formation of Muslim identity in Western educational environments. Employing qualitative, library-based research, this research engages critically academic literatures, seminal texts, and the works of modern Muslim thinkers. The results show that secularism not only impacts the marginalization of Islamic values ​​in the curricula but also affects the identity formation experienced by Muslim students in their search for identity. Islamic education in the West is required not only to be a space for the transmission of religious knowledge but also to become a space for the formation of a strong religious identity. The novelty of this research lies in its exploration of Muslim identity formation in the West within the prism of contemporary Islamic discourse, thereby offering new perspectives in understanding the dynamics of the Muslim identity crisis and contextual educational strategies amidst the currents of global secularism.